2014
DOI: 10.1002/pchj.60
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant functional connectivity of the hippocampus in older adults with subthreshold depression

Abstract: Major depression disorder (MDD) is closely associated with functional and structural changes in the hippocampus (HC). Neuroimaging studies have demonstrated abnormal functional connectivity (FC) of the HC in patients with MDD, but it remains unknown whether this abnormal hippocampal FC pattern occurs in individuals with subthreshold depression (StD) who are at high risk of MDD. Resting-state functional magnetic resonance imaging data were collected from 19 elderly individuals with StD and 18 normal controls. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…Previous studies found decreased hippocampal connectivity to frontal regions, which correlated with depression symptoms, specifically in StD subjects. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found decreased hippocampal connectivity to frontal regions, which correlated with depression symptoms, specifically in StD subjects. 48 …”
Section: Discussionmentioning
confidence: 99%
“…One study confirmed that the functional connectivity of the hippocampus to the prefrontal and cuneus cortices decreased substantially in older adults with sub-threshold depression. Besides, the strength of hippocampus-cuneus connectivity was correlated with selfreported depressive symptoms [40]. This indicates that dysfunctional integration within the hippocampus and the cortical regions may involve in the occurrence of depression.…”
Section: The Role Of Neural Circuitry In Other Brain Regions Under a mentioning
confidence: 81%
“…Recent studies documented that the dysfunction of the neural circuits between the prefrontal and bilateral parietal cortex was associated with cognitive impairment in depression [51] [52]. The role of individual neural circuitry between different brain regions in depression was further emphasized by the relationship between the strength of hippocampus-cuneus connectivity and self-reported depressive symptoms in elderly individuals with sub-threshold depression [40]. These studies indicate the neural circuitry mechanism of depression is likely due to the elaborate interactions between the individual neural circuitry in different brain regions, even in the whole brain networks [53].…”
Section: Perspectivesmentioning
confidence: 99%
“…Great efforts have been made during the past decades with an aim to decipher the underlying mechanism of this mental disease [5][6][7][8][9][10][11]. The occurrence of depression was usually accompanied with several changes in the prefrontal limbic areas which mainly involved the orbitofrontal cortex, insula, anterior and posterior cingulate cortex, hippocampus, amygdala and thalamus [12,13].…”
Section: Introductionmentioning
confidence: 99%